The folklorist in the marketplace: conversations at the crossroads of vernacular culture and economics - Mullins, Willow G., editor; Batra-Wells, Puja, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Voices from multiple disciplines consider how economics shape and are shaped by folk groups and academic disciplines and goes far beyond the well-trod examinations of material culture to look closely at the historical and contemporary intersections of these two disciplines and provoke cross-disciplinary conversation and collaboration.--Provided by publisher.
Folklore as a networked economy: or, how a recently-invented-but-traditional artifact reveals the way folkloric production has always worked / John laudun -- Branding unibroue: selling Québécois folklore through beer / Julie M-A Leblanc -- Market forces and marketplace economics at the Smithsonian Folklife Festival / Halle M. Butvin and James I. Deutsch -- The sweet spot: an epistemological approach to the economics of sugarmaking in Vermont / Michael Lange -- Where the creel boats go: the politics of sustainable fisheries in a small Orkney community / Christofer Johnson -- The economics of curation and representation: dialogues in the commemorative landscape of Portsmouth, Ohio / Cassie Patterson -- An ordered mess / Yuanhao Zhao -- Art/work: precarious encounters and vernacular economic remedies / Puja Batra-Wells -- From vision to implementation: clashing values of economic idealism and solvency in Twin Oaks community, 1967/1979 / Rahima Schwenkbeck -- "Why the sea is salty": folktales as sources of grassroots economics / Irene Sotiropoulou -- What would hermes do?: a Jungian perspective on the trickster and business ethics / William A. Ashton -- Folk economies and the artisan workshop / Amy Shuman -- Consuming authenticities: an economics of folklorists / Willow G. Mullins.
Keywords: Folklore -- Economic aspects; Material culture -- Economic aspects; Markets -- Folklore